Higher serum level of Cystatin C: an additional risk factor of CAD - Chen, Zhenfei; Zhang, Jing; Feng, Jun; Zhou, Gaoliang; Jin, Xiaoqin; Pan, Jianyuan (Medicine, 2021)
Cystatin C has been proposed as a useful biomarker of early impaired kidney function and a predictor of mortality risk. The present study is to investigate the association between serum Cystatin C and the severity of coronary artery lesions, Gensini score (GS), and the risk of coronary artery disease (CAD). - A total of 682 CAD patients (230 females, 452 males; mean age 62.6 ± 10.7 years, range from 31 to 86 years) and 135 controls (41 females, 94 males; mean age 58.0 ± 10.3 years, range from 38 to 84 years) were recruited in the present study. Enzyme-linked immunosorbent assay was applied to measure serum cystatin C levels and other serum indexes. The estimated glomerular filtration rate and GS were calculated. - Serum low-density lipoprotein cholesterol (LDL-C), uric acid, Cystatin C, and homocysteine (HCY) were significantly elevated in CAD patients compared to controls. There were significant differences regarding total cholesterol, triglyceride, high-density lipoprotein, low-density lipoprotein, cystatin C, eGFR and GS among stable angina pectoris (SAP), unstable angina group (UAP), and acute myocardial infarction (AMI) patients. AMI group had an elevated serum Cystatin C, LDL-C, HCY, and GS than SAP and UAP patients. When stratified patient groups by the quartiles of Cystatin C, we found age, the proportion of male and patients with diabetes, HCY, and GS were increased in Q4 than in other quartile groups. Spearman correlation test revealed a positive relationship between Cystatin C, HCY, and GS. Multivariate logistic regression analysis revealed that serum Cystatin C level, presence of hypertension and diabetes, HCY, age, and male were the risk factors for coronary artery lesions. - In summary, our results suggested that cystatin C is a promising clinical biomarker that provides complementary information to the established risk determinants. The serum Cystatin C level is strongly associated with GS and could be used to evaluate the severity of coronary artery lesions.